(untitled) (Medicine Today, 2022)
Introduction: This retrospective descriptive cross-sectional study was done to see upper gastrointestinal endoscopic findings in patients presenting with dysphagia. Materials and Methods: Reports of patients undergoing upper gastrointestinal endoscopy were retrieved from endoscopy records. Data regarding age, gender, and endoscopic features and impressions were collected. The data analysis was done using IBM SPSS® v21 (IBM, Armonk, New York). Frequency, proportions, mean ± SD, and range were calculated. Results: Out of 147 participants, the mean age of the participants was 53.46 ± 15.99 years. There was an equal proportion of participants of each gender (50.3% female and 49.6% male). The prevalence of endoscopic abnormalities was 93.8%. Most of the participants had carcinoma esophagus (38.7%, 57) followed by gastritis (35.3%, 52), gastric polyp (10.8%, 16), and duodenitis (8.8%, 13). Conclusion: Dysphagia is an alarming symptom that warrants prompt evaluation. With diagnostic and therapeutic value, upper GI (gastrointestinal) endoscopy remains a rapid initial effective tool in the evaluation of patients with dysphagia. Medicine Today 2022 Vol.34(2): 136-139